Language Phenomenon in Classroom Learning Process: A Study at MAN Model State Islamic Senior High School Gorontalo - Sayama Malabar (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This present study is devoted to investigating the language phenomenon focusing on spoken communication during the classroom learning at MAN Model State Islamic Senior High School, Gorontalo. Employing a descriptive qualitative method, the data of this study encompassed the utterances of the teacher and students during the classroom learning, specifically in UN (national examination) subjects. The data were generated by a conversation method with its basic techniques, i.e., recording, and note-taking. Furthermore, the data were qualitatively analyzed by (1) transcribing the recording into a written discourse, (2) grouping the data according to the problem statement, (3) examining the data, and (4) summing up. This study successfully identifies four strategies used during the communication process in a classroom learning; the strategies are (1) bald on record, (2) positive politeness, (3) negative politeness, and (4) off record.